Zircon ages delimit the provenance of a sand extrudite from the Botucatu Formation in the Paraná volcanic province, Iraí, Brazil - Pinto, V.; Hartmann, L.; Santos, J.; McNaughton, Neal (Academia Brasileira de Ciencias, 2015)
Ion microprobe age determinations of 102 detrital zircon crystals from a sand extrudite, Cretaceous Paraná volcanic province, set limits on the origin of the numerous sand layers present in this major flood basalt province. The zircon U-Pb ages reflect four main orogenic cycles: Mesoproterozoic (1155-962 Ma), latest Proterozoic-early Cambrian (808-500 Ma) and two Palaeozoic (Ordovician– 480 to 450 Ma, and Permian to Lower Triassic– 296 to 250 Ma). Two additional small concentrations are present in the Neoarchean (2.8 to 2.6 Ga) and Paleoproterozoic (2.0 to 1.7 Ga). Zircon age peaks closely match the several pulses of igneous activity in the Precambrian Brazilian Shield and active orogeny in Argentina. A main delimitation of the origin of the sand is the absence of zircon ages from the underlying Cretaceous basalts, thus supporting an injectite origin of the sand as an extrudite that emanated from the paleoerg that constitutes the Botucatu Formation.